Educational space as object of socio-geographical research - Bilous, Yurii; Bilous, Victoriia (Human Geography Journal, 2022)
The relevance of the study of the general educational space is strengthened by the fact that significant transformations are currently taking place in the general educational space as a component of the social space, which are taking place in parallel with the implementation of the decentralization reform. The article analyzes socio-geographical approaches to the study of the concept of general educational space, which we propose to consider as a component of educational space, from the point of view of general secondary education institutions. The place of educational space, as a component of geospace, is outlined in the socio-economic space, because it is the result of the interaction of social and economic spaces. The study identified local centers of the educational space that belong to educational institutions. The concept of "general educational space" is characterized, which we propose to define as the territory on which general secondary education institutions of various types and forms, as well as participants of the educational process, which ensure the implementation of educational activities, function, organize the general educational process and interact with each other. We determined the structure and properties of the general educational space. We propose to consider the structure of the general educational space as three-dimensional, highlighting at the same time such components (dimensions) as: territorial placement of educational institutions; participants in the general education process; the quality of providing educational services. General educational space, as a component of geospace, is characterized by such indicators as: length, dynamism, structure and continuity. Quantitative and qualitative indicators of the functioning of the general educational space were described. Characterization of the structure of the general educational space of the regional region, which plays a special role in the study of the development of education, was carried out. The general educational space has the potential that creates the foundation of national security, ensures the competitiveness of the country, the region among other national state bodies.